New insights into the relationship between structure and photocatalytic properties of TiO2 catalysts - Veres Ágnes (RSC ADVANCES, 2015)
This work systematically investigated the relationship between structure, morphology, photoelectrochemical (PEC) and photocatalytic (PC) properties of TiO2 catalysts. A series of TiO2 catalysts with various phase compositions (anatase-, brookite- and finally rutile-rich samples) and morphologies (1D morphology, rhomboid nanoparticles (NPs) and flower-like assemblies of nanorods) were prepared by an acidic hydrothermal treatment of hydrogen titanate nanofibres (H-TNFs). The structures of the samples, such as crystal phase composition and their spatial distribution, were extensively characterised, and the samples were tested for photocatalytic degradation of ethanol. A strong correlation is found between PEC and PC properties. PEC measurements revealed that the brookite-rich samples generated high but unstable photocurrents. The anatase and rutile-rich samples showed good stability, but for the rutile-rich samples low photocurrents were detected due to the poor conductivity of this polymorph. In contrast, the sample containing 93.2% anatase and 6.8% brookite with elongated morphology not only showed the ability to generate high photocurrents but also maintained a stable photoresponse upon an extended period of time, because of its well-balanced bi-crystalline structure and elongated morphology. Therefore, the abilities to generate high photocurrents and to maintain a stable photoresponse are equally important and probably a prerequisite for a good photocatalyst.